2019
DOI: 10.1111/nep.13591
|View full text |Cite
|
Sign up to set email alerts
|

Paclitaxel‐coated balloon in the treatment of recurrent dysfunctional arteriovenous access, real‐world experience and longitudinal follow up

Abstract: Aim Dysfunctional arteriovenous (AV) access remains a significant cause of morbidity and hospital admission for patients with end stage renal failure on haemodialysis. This study was performed to evaluate the impact of paclitaxel‐coated Balloon (PCB) on the patency of AV access with recurrent stenoses. Methods We retrospectively studied haemodialysis patients who presented to our centre with recurrent AV access dysfunction and compared intervention‐free patency using plain balloon versus PCB. Results A total o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…Previous studies have demonstrated that DCB and CtB are superior to conventional balloon (CB) in terms of AVF stenosis. [2][3][4] However, studies comparing the effects of HPB and CB were scarce. Therefore, we conducted a meta-analysis to investigate the clinical effectiveness of HPB against CB for patients with AVF stenosis.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that DCB and CtB are superior to conventional balloon (CB) in terms of AVF stenosis. [2][3][4] However, studies comparing the effects of HPB and CB were scarce. Therefore, we conducted a meta-analysis to investigate the clinical effectiveness of HPB against CB for patients with AVF stenosis.…”
Section: Introductionmentioning
confidence: 99%
“…21 Supporting Information Table S1 summarizes the literature comparison results. 6,[20][21][22][23] The observation of comparable target lesion primary patency in the FLEX-AV registry relate to those reported by RCTs is remarkable given that inclusion criteria for RCTs are more stringent than those for this allcomers registry. Thus, the results provide reinforcement for the benefit of FLEX VP prior to PTA for vascular access treatment.…”
Section: Discussionmentioning
confidence: 87%
“…These data were confirmed in a longitudinal follow-up of 147 patients. 49 There has been concern about morbidity and mortality with DCB; however, a recent meta-analysis, ILLUMENATE, found mortality rates for patients treated with DCB and uncoated PTA were indistinguishable over 3-year follow up. 50 Certainly, additional studies are needed.…”
Section: Secondary Patencymentioning
confidence: 99%